Application performance and innovation effect of ESG indicators in corporate governance under the background of green development: Take Tesla Electric Vehicle Co - Zhang, Xiaoyue (International Journal of Global Economics and Management, 2024)
With the development of globalization, enterprises increasingly pay attention to the impact of environment, society and governance (ESG) on their performance. In this paper, the key ESG issues of Tesla is discussed in depth by means of case study, and the implementation situation is analyzed in detail from multiple perspectives. Research shows that the application of ESG technology can significantly improve the financial situation of enterprises and promote their long-term development. This paper obtains the result that the new energy vehicle industry actively improves its own companies to achieve the purpose of ESG excellent rating. It will become an important development trend for enterprises to actively respond to ESG goals. Based on practical cases, this paper summarizes the experience and les-sons of ESG technology implementation in energy enterprises, and puts forward corresponding normative suggestions on ESG information disclosure.